Preparation method of composite membrane electrode, composite membrane electrode and battery
Through a simplified preparation method, composite film electrodes are prepared by mixing materials such as conductive agents, active substances and organic carbon sources, which solves the problems of poor flexibility, low conductivity and capacity of membrane electrodes in the prior art, and realizes a composite film electrode with high flexibility, excellent conductivity and high capacity.
Patent Information
- Application Number
- CN202411810103.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the method for preparing flexible self-supporting film electrodes is complicated and complicated, and the resulting film electrodes have poor flexibility, low conductivity and capacity.
By mixing conductive agent, active substance, organic carbon source, tackifier and solvent, a cast film liquid is prepared, the solvent is removed to form a wet film, and then cured and carbonized to obtain a composite film electrode. This method simplifies the preparation process and improves the flexibility and capacity of the membrane electrode.
The composite film electrode has high flexibility, excellent conductivity and high capacity, avoiding the use of adhesives and conductive agents, reducing operating costs and energy consumption, and is suitable for industrial production.
Smart Images

Figure CN119812219A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a method for preparing a composite membrane electrode, a composite membrane electrode and a battery. Background Art
[0002] With the continuous development of intelligent technology, wearable electronic devices have gradually appeared in various fields and will become the mainstream trend of the development of smart products in the future. However, one of the biggest challenges in the development of wearable devices is the flexible energy storage devices that are compatible with them. Electrode materials are the key factors that determine the performance of flexible energy storage devices. Among them, self-supporting flexible membrane electrode materials, as an important component of flexible energy storage devices, have received extensive attention from scientific researchers and have become a research focus.
[0003] However, in the prior art, the preparation method of flexible self-supporting membrane electrodes is complicated and cumbersome, and the resulting membrane electrodes have poor flexibility and low capacity. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, one object of the present invention is to provide a method for preparing a composite membrane electrode, a composite membrane electrode, and a battery. The method provided in the present application is simple, and the obtained composite membrane electrode has good flexibility and high capacity.
[0005] In one aspect of the present invention, the present invention provides a method for preparing a composite membrane electrode. According to an embodiment of the present invention, the method comprises: mixing a conductive agent, an active substance, an organic carbon source, a thickener and a solvent to obtain a casting solution; removing the solvent from the casting solution to obtain a wet film; and curing and carbonizing the wet film to obtain a composite membrane electrode.
[0006] According to the method of the above embodiment of the present invention, after preparing the casting solution, the solution in the casting solution is removed, and the casting solution is phase separated to form a wet film with a mutually penetrating network structure, which can not only provide a good electrolyte transmission channel, but also relieve the deformation stress of the composite membrane electrode, and ensure the flexibility of the composite membrane electrode. In the subsequent curing and carbonization process, the organic matter (organic carbon source, thickener, etc.) in the wet film will undergo a pyrolysis reaction to release small molecular compounds (such as H2O, NH3, etc.), which can form a rich pore structure, provide a large specific surface area, and enhance the capacity of the active material, thereby increasing the effective utilization of the active material, thereby increasing the capacity of the electrode, and in the process of carbonization, the carbon atoms will rearrange to form a carbon skeleton structure, which can be used for the load of the active material, and can reduce the risk of the active material volume expansion and contact with the electrolyte, and enhance the safety performance of the battery. The composite film obtained by the above method has the characteristics of ultra-thin, flexible, self-supporting and developed multi-level pore structure, can be directly used as an electrode material, avoids the use of binders and conductive agents in the preparation process of battery negative electrode materials, and solves the shortcomings of low flexibility, low strength, low conductivity and low capacity of general composite materials. At the same time, the method of the present application reduces operating costs and energy consumption, and ensures the output of the composite membrane electrode, which is conducive to industrial production.
[0007] In addition, the method according to the above embodiment of the present invention may also have the following additional technical features:
[0008] In some embodiments of the present invention, the mass ratio of the organic carbon source, the thickener, the conductive agent and the active material is (10-18): (5.26-17.65): (0.1-1): (0.1-1). Thus, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0009] In some embodiments of the present invention, the mass proportion of the organic carbon source is 5%-25% based on the total mass of the casting solution. Thus, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0010] In some embodiments of the present invention, the residual carbon rate of the organic carbon source is 35%-55%. Thus, the risk of carbon skeleton collapse in the subsequent carbonization process can be effectively avoided, which is conducive to obtaining a self-supporting composite membrane electrode.
[0011] In some embodiments of the present invention, the organic carbon source includes polyacrylonitrile, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0012] In some embodiments of the present invention, the degree of polymerization of the viscosity enhancer is 13-96. This can increase the cohesiveness of the casting solution, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0013] In some embodiments of the present invention, the viscosity enhancer includes polyvinyl pyrrolidone, thereby increasing the cohesiveness of the casting solution, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0014] In some embodiments of the present invention, the conductive agent includes at least one of graphene, carbon nanotubes and carbon black, thereby facilitating the production of a composite membrane electrode with good flexibility and good conductivity.
[0015] In some embodiments of the present invention, the active material includes at least one of silicon dioxide, tin dioxide and silicon, thereby facilitating the improvement of the capacity of the composite membrane electrode.
[0016] In some embodiments of the present invention, the solvent includes N,N-dimethylformamide, which is conducive to forming a uniform casting solution and facilitating the subsequent formation of a composite membrane motor.
[0017] In some embodiments of the present invention, the step of removing the solvent in the casting solution to obtain a wet film comprises:
[0018] After the casting solution is scraped, it is placed in an aqueous slow-release agent, so that the solvent in the casting solution enters the aqueous slow-release agent to obtain a wet film, thereby facilitating the production of a composite membrane electrode with good flexibility, good conductivity and high capacity.
[0019] In some embodiments of the present invention, the thickness of the scraping film is 50 μm-300 μm. Thus, the prepared composite membrane electrode can have better flatness and thickness, which is conducive to ensuring the flexibility of the composite membrane electrode.
[0020] In some embodiments of the present invention, the aqueous sustained-release agent includes water and a sustained-release agent, and based on the total mass of the aqueous sustained-release agent, the mass proportion of the sustained-release agent is 40%-80%. Thus, the exchange rate between water and the polymer solvent in the casting solution can be slowed down, which is conducive to ensuring the flexibility of the composite membrane electrode.
[0021] In some embodiments of the present invention, the sustained-release agent includes at least one of an ethanol aqueous solution, an ethylene glycol aqueous solution, and an N,N-dimethylformamide aqueous solution, thereby promoting the movement and mutual diffusion of polymer chain segments and improving the flexibility and mechanical strength of the composite membrane electrode.
[0022] In some embodiments of the present invention, the curing temperature is 180° C.-280° C. This is beneficial to the volatilization of water in the wet film, and can form a porous structure, which is beneficial to accommodating active substances and improving the capacity of the composite membrane electrode.
[0023] In some embodiments of the present invention, the curing temperature rise rate is 1°C / min-3°C / min. This can promote the movement of polymer chain segments in the wet film, accelerate the degree of cross-linking between soluble groups to form a three-dimensional network structure, and facilitate the acquisition of a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0024] In some embodiments of the present invention, the curing time is 1.5h-2.5h. Thus, it can be ensured that there is more time for the polymer soluble groups in the wet film to undergo cross-linking reaction, thereby increasing the degree of cross-linking of the polymer in the wet film, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0025] In some embodiments of the present invention, the carbonization temperature is 900° C.-1200° C. Thus, sufficient energy can be provided to cause the carbon atoms in the membrane to overcome the potential barrier and rearrange to form a carbon-based skeleton structure, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0026] In some embodiments of the present invention, the heating rate of the carbonization is 3°C / min-4°C / min. Thus, the speed and degree of carbon atom rearrangement can be controlled, thereby affecting the carbonization degree of the membrane, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0027] In some embodiments of the present invention, the carbonization time is 50 min-80 min, thereby ensuring that the carbon atoms in the membrane have enough time to rearrange, which is conducive to forming a carbon-based skeleton structure and obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0028] In the second aspect of the present invention, the present invention provides a composite membrane electrode. According to an embodiment of the present invention, the composite membrane electrode is prepared by the above method, and thus the alumina microspheres obtained in the present application have a higher crushing strength.
[0029] In some embodiments of the present invention, the thickness of the composite membrane electrode is 10 μm-50 μm.
[0030] In a third aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery comprises the composite membrane electrode prepared by the above method and the above composite membrane electrode.
[0031] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0033] Figure 1 A flow chart of a method for preparing a composite membrane electrode according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0034] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0035] With the continuous development of intelligent technology, wearable electronic devices have gradually appeared in various fields and will become the mainstream trend of the development of smart products in the future. However, one of the biggest challenges in the development of wearable devices is the flexible energy storage devices that are compatible with them. Electrode materials are the key factors that determine the performance of flexible energy storage devices. Among them, self-supporting flexible membrane electrode materials, as an important component of flexible energy storage devices, have received extensive attention from scientific researchers and have become a research focus.
[0036] However, in the prior art, the preparation method of flexible self-supporting membrane electrodes is complicated and cumbersome, and the resulting membrane electrodes have poor flexibility, low conductivity and capacity.
[0037] In one aspect of the present invention, the present invention provides a method for preparing a composite membrane electrode. Figure 1 , the method comprising:
[0038] S100, mixing a conductive agent, an active material, an organic carbon source, a thickener and a solvent to obtain a casting solution.
[0039] In this step, a casting liquid can be obtained by mixing a conductive agent, an active substance, an organic carbon source, a thickener and a solvent. Specifically, the organic carbon source and the solvent are first mixed and dissolved to obtain a mixed solution, and then the conductive agent and the active substance are evenly dispersed in the mixed solution. The even dispersion of the conductive agent can effectively reduce the resistance of the electrode and form a conductive network, so that the current can be transmitted more smoothly in the electrode material, thereby improving the conductivity of the composite membrane electrode. The even dispersion of the active substance can undergo redox reactions during the charge and discharge process of the battery to achieve energy storage and release. Finally, the thickener is added to improve the fluidity of the casting liquid, improve the adhesion of the casting liquid, and facilitate the subsequent film-forming reaction.
[0040] According to some embodiments of the present invention, the mass ratio of the organic carbon source, the tackifier, the conductive agent and the active material is (10-18): (5.26-17.65): (0.1-1): (0.1-1). For example, it can be 10: 5.26: 0.1: 0.1, 15: 5.26: 0.1: 0.1, 18: 5.26: 0.1: 0.1, 10: 10: 0.1: 0.1, 10: 17.65: 0.1: 0.1, 10: 5.26: 0.5: 0.1, 10: 5.26: 1: 0.1, 10: 5.26: 0.1: 0.5, 10: 5.26: 0.1: 1, etc. The addition of active materials can realize the storage and release of energy, and the addition of conductive agents can effectively reduce the composite film. The resistance of the electrode is increased, and the conductivity of the composite membrane electrode is improved. The addition of the organic carbon source is conducive to the formation of the subsequent carbon skeleton structure, and has a rich pore structure, which can not only enhance the capacity of the active substance and improve the capacity of the composite membrane electrode, but also relieve the deformation stress of the composite membrane electrode and ensure the flexibility of the composite membrane electrode. The active substance and the conductive agent can also be distributed in the pores, which can further reduce the risk of the active substance volume expansion and contact with the electrolyte. In addition, the carbon skeleton has excellent conductive properties, so that the composite membrane electrode has good conductivity. Therefore, by limiting the mass ratio between the organic carbon source, the thickener, the conductive agent and the active substance, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0041] According to some embodiments of the present invention, based on the total mass of the casting solution, the mass proportion of the organic carbon source is 5%-25%. For example, it can be 5%, 8%, 10%, 15%, 20%, 25%, etc., and the mass proportion of the organic carbon source is limited to the above range, which can control the cross-linking points between the organic carbon source molecules, which is conducive to the formation of the subsequent carbon skeleton structure, so that the carbon skeleton has a rich pore structure, which can not only enhance the capacity of the active substance, improve the capacity of the active composite membrane electrode, but also relieve the deformation stress of the composite membrane electrode, ensure the flexibility of the composite membrane electrode, and the active substance and the conductive agent can also be distributed in the pores, which can further reduce the risk of the active substance volume expansion and contact with the electrolyte. In addition, the carbon skeleton has excellent conductive properties, so that the composite membrane electrode has good conductivity. Therefore, by limiting the mass proportion of the organic carbon source to the above range, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0042] According to some embodiments of the present invention, the residual carbon rate of the organic carbon source is 35%-55%, for example, it can be 35%, 40%, 45%, 50%, 55%, etc. By limiting the residual carbon rate of the organic carbon source within the above range, the carbon atoms can have a stronger interaction force, which can effectively avoid the risk of carbon skeleton collapse in the subsequent carbonization process, which is conducive to obtaining a self-supporting composite membrane electrode, thereby ensuring the flexibility of the composite membrane electrode.
[0043] According to some embodiments of the present invention, the organic carbon source includes polyacrylonitrile, and the polyacrylonitrile molecular chain is connected by acrylonitrile as units. Due to the strong polarity -C≡N on the polyacrylonitrile molecular group, the cohesive energy is large, the thermal stability is high, the residual carbon rate is high, and it is easy to form a film after sintering.
[0044] According to some embodiments of the present invention, the degree of polymerization of the thickener is 13-96, for example, 13, 20, 30, 50, 80, 90, 96, etc. Limiting the degree of polymerization of the thickener within the above range can improve the fluidity of the casting solution, improve the adhesion of the casting solution, and facilitate the subsequent film-forming reaction. Thus, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0045] According to some embodiments of the present invention, the viscosity enhancer includes polyvinyl pyrrolidone. Polyvinyl pyrrolidone has good bonding properties, can improve the fluidity of the casting solution, improve the adhesion of the casting solution, and is beneficial to the subsequent film-forming reaction. Thus, a composite membrane electrode with good flexibility, high conductivity and high capacity can be obtained.
[0046] According to some embodiments of the present invention, the conductive agent includes at least one of graphene, carbon nanotubes and carbon black. The conductive agent can effectively reduce the resistance of the composite membrane electrode and form a conductive network, which can improve the conductivity of the composite membrane electrode. It can also be coated on the surface of the active material, which is conducive to alleviating the volume change of the active material during the charge and discharge process, and improves the safety performance of the battery. In addition, the conductive agent has excellent flexibility and good conductivity. Therefore, the selection of the conductive agent is conducive to obtaining a composite membrane electrode with good flexibility and good conductivity.
[0047] According to some embodiments of the present invention, the active material includes at least one of silicon dioxide, tin dioxide and silicon. The above active material has a relatively high theoretical capacity, has a safer lithium insertion potential, is non-toxic and easy to obtain, and thus, the selection of the above active material is conducive to improving the capacity of the composite membrane electrode.
[0048] According to some embodiments of the present invention, the solvent includes N,N-dimethylformamide. The above solvent can effectively dissolve the organic carbon source, which is conducive to forming a uniform casting solution and facilitating the subsequent formation of a composite membrane electrode.
[0049] S200, removing the solvent in the casting solution to obtain a wet film.
[0050] In this step, the solvent in the casting solution is removed to promote phase separation of the casting solution, forming a mutually penetrating network structure, which is conducive to the formation of a wet film.
[0051] In some embodiments of the present application, step S200 further includes:
[0052] After the casting liquid is scraped, it is placed in an aqueous slow-release agent, so that the solvent in the casting liquid enters the aqueous slow-release agent to obtain a wet film.
[0053] In this step, the casting liquid is scraped and then placed in an aqueous slow-release agent, which can induce the casting liquid to phase separate and form a porous wet film structure.
[0054] According to some embodiments of the present invention, the thickness of the scraping film is 50μm-300μm, for example, it can be 50μm, 100μm, 150μm, 200μm, 250μm, 300μm, etc. By limiting the thickness of the scraping film within the above range, the diffusion rate and curing time of the polymer in the casting liquid in the aqueous sustained release agent can be controlled, thereby affecting the thickness and uniformity of the composite membrane electrode. The exchange rate and degree between the solvent and water in the casting liquid can also be adjusted, thereby controlling the pore structure and pore size distribution of the composite membrane electrode.
[0055] According to some embodiments of the present invention, the aqueous sustained-release agent includes water and a sustained-release agent. Based on the total mass of the aqueous sustained-release agent, the mass proportion of the sustained-release agent is 40%-80%. For example, the mass concentration of the aqueous sustained-release agent can be 40%, 50%, 60%, 70%, 80%, etc. By limiting the mass concentration of the sustained-release agent within the above range, the double diffusion rate of water and the polymer solvent in the casting solution can be slowed down, which is beneficial to ensure the flexibility of the composite membrane electrode.
[0056] According to some embodiments of the present invention, the sustained-release agent includes at least one of an ethanol aqueous solution, an ethylene glycol aqueous solution, and an N,N-dimethylformamide aqueous solution. In the process of removing the solvent in the casting solution, the presence of the sustained-release agent can slow down the double diffusion rate of the solvent and water of the polymer in the casting solution to form a well-structured membrane material.
[0057] S300: solidifying and carbonizing the wet film to obtain a composite membrane electrode.
[0058] In this step, by curing the wet film, the soluble groups in the wet film can be induced to undergo cross-linking reactions to form a more stable network structure, thereby improving the mechanical strength and flexibility of the composite membrane electrode. The cured carbon film is then carbonized. During the carbonization process, the carbon atoms in the film are rearranged to form a carbon-based skeleton structure with high stability, which can further improve the mechanical strength of the composite membrane electrode. In addition, the formed carbon skeleton structure has a rich pore structure, which provides a large specific surface area and enhances the capacity of the active material, thereby increasing the effective utilization of the active material, thereby improving the capacity of the composite membrane electrode. On the other hand, it can also reduce the risk of the active material volume expansion and contact with the electrolyte, thereby enhancing the safety performance of the battery.
[0059] According to some embodiments of the present invention, the curing temperature is 180°C-280°C. For example, it can be 180°C, 200°C, 230°C, 250°C, 280°C, etc. By controlling the curing temperature, the segment movement of the polymer in the wet film can be promoted, the degree of cross-linking between the soluble groups can be accelerated, and it is beneficial to form a three-dimensional network structure. Moreover, the above curing temperature is beneficial to the volatilization of water in the wet film, and a porous structure can be formed, which is beneficial to accommodating active substances and improving the capacity of the composite membrane electrode.
[0060] According to some embodiments of the present invention, the curing heating rate is 1°C / min-3°C / min. For example, it can be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, etc. By limiting the curing heating rate, the segment movement of the polymer in the wet film can be promoted, the cross-linking degree between the soluble groups can be accelerated, and it is conducive to the formation of a three-dimensional network structure.
[0061] According to some embodiments of the present invention, the curing time is 1.5h-2.5h. For example, it can be 1.5h, 1.8h, 2h, 2.5h, etc. By limiting the curing time, it can be ensured that there is more time for the cross-linking reaction between the polymer soluble groups in the wet film, thereby improving the cross-linking degree of the polymer polymers in the wet film.
[0062] According to some embodiments of the present invention, the carbonization temperature is 900°C-1200°C. For example, it can be 900°C, 1000°C, 1100°C, 1200°C, etc. By limiting the carbonization temperature, sufficient energy can be provided to cause the carbon atoms in the membrane to overcome the potential barrier and rearrange to form a carbon-based skeleton structure, which has high stability and can further improve the mechanical strength of the composite membrane electrode. In addition, the formed carbon skeleton structure has a rich pore structure, which provides a large specific surface area on the one hand, enhances the capacity of the active material, thereby increasing the effective utilization of the active material, and then improving the capacity of the composite membrane electrode. On the other hand, it can also reduce the risk of the active material volume expansion and contact with the electrolyte, thereby enhancing the safety performance of the battery.
[0063] According to some embodiments of the present invention, the heating rate of carbonization is 3°C / min-4°C / min. For example, it can be 3°C / min, 3.3°C / min, 3.5°C / min, 3.8°C / min, 4°C / min, etc. By controlling the heating rate of carbonization, the speed and degree of carbon atom rearrangement can be controlled, thereby affecting the carbonization degree of the membrane, which is conducive to obtaining a composite membrane electrode with good flexibility, high conductivity and high capacity.
[0064] According to some embodiments of the present invention, the carbonization time is 50min-80min. For example, it can be 50min, 60min, 70min, 80min, etc. By limiting the carbonization time, it can be ensured that the carbon atoms in the membrane have enough time to rearrange, which is conducive to the formation of a carbon-based skeleton structure, has high stability, can further improve the mechanical strength of the composite membrane electrode, and the formed carbon skeleton structure has a rich pore structure, on the one hand, provides a large specific surface area, enhances the capacity of the active material, thereby increasing the effective utilization of the active material, and then improves the capacity of the composite membrane electrode, on the other hand, it can also reduce the risk of the active material volume expansion and contact with the electrolyte, and enhance the safety performance of the battery.
[0065] According to the method of the above embodiment of the present invention, after preparing the casting liquid, the solution in the casting liquid is removed to promote phase separation of the casting liquid, forming a wet film with a network structure that penetrates each other, which can not only provide a good electrolyte transmission channel and improve the conductivity of the composite membrane electrode, but also relieve the deformation stress of the composite membrane electrode and ensure the flexibility of the composite membrane electrode. In the subsequent curing and carbonization process, the organic matter (organic carbon source, thickener, etc.) in the wet film will undergo a pyrolysis reaction to release small molecular compounds (such as H2O, NH3, etc.), which can form a rich pore structure, provide a large specific surface area, and enhance the activity. The capacity of the material to accommodate the material, thereby increasing the effective utilization of the active material, and then increasing the capacity of the electrode, and in the process of carbonization, the carbon atoms will rearrange to form a carbon skeleton structure, which can be used for the load of the active material, and can reduce the risk of the active material volume expansion and contact with the electrolyte, and enhance the safety performance of the battery. The composite film obtained by the above method has the characteristics of ultra-thin, flexible, self-supporting and developed multi-level pore structure, and can be directly used as an electrode material, avoiding the use of binders and conductive agents in the preparation process of battery negative electrode materials, and solving the shortcomings of low flexibility, low strength, low conductivity and low capacity of general composite materials. At the same time, the method of the present application reduces operating costs and energy consumption, and ensures the output of composite membrane electrodes, which is conducive to industrial production.
[0066] In the second aspect of the present invention, the present invention proposes a composite membrane electrode. According to an embodiment of the present invention, the composite membrane electrode is prepared by the above method. Therefore, the method provided by the present application is simple, and the obtained composite membrane electrode has good flexibility, high conductivity and high capacity, so that the composite membrane electrode has good flexibility, high conductivity and high capacity. It should be noted that the features and advantages described above for the preparation method of the composite membrane electrode are also applicable to the composite membrane electrode, and will not be repeated here.
[0067] According to some embodiments of the present invention, the thickness of the composite membrane electrode is 10 μm-50 μm. For example, it can be 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, etc. By limiting the thickness of the composite membrane electrode to the above range, the content of active substances in the composite membrane electrode can be guaranteed, which is conducive to improving the capacity of the composite membrane electrode and ensuring the flexibility of the composite membrane electrode.
[0068] In the third aspect of the present invention, the present invention provides a battery. According to an embodiment of the present invention, the battery adopts the composite membrane electrode prepared by the above method or adopts the above composite membrane electrode. As a result, the composite membrane electrode has good flexibility, high conductivity and high capacity, so that the battery has good capacity performance. It should be noted that the features and advantages described above for the composite membrane electrode and its preparation method are also applicable to the battery, and will not be repeated here.
[0069] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.
[0070] Example 1
[0071] Preparation of composite membrane electrode:
[0072] 1) Weigh 3.6 g of an organic carbon source with a residual carbon rate of 40%, dissolve it in a solvent at 80°C, add a conductive agent and an active substance, mix them evenly, and continue to add 3.53 g of a thickener with a degree of polymerization of 90 to the above solution, dissolve it evenly, and obtain a casting solution; wherein the organic carbon source is polyacrylonitrile, the solvent is N,N-dimethylformamide, the conductive agent is graphene, the active substance is silicon dioxide, and the thickener is polyvinyl pyrrolidone.
[0073] 2) After cooling the casting solution to 20° C., a film is scraped on a glass plate with a film thickness of 100 μm, and a coagulation bath is performed in a 20° C. aqueous sustained-release agent, and a wet film is obtained after immersion precipitation phase transformation, wherein the aqueous sustained-release agent is a 50% ethanol aqueous solution;
[0074] 3) After freeze-drying the wet film, the temperature was increased to 300°C at a heating rate of 1°C / min in an air atmosphere and kept constant at this temperature for 60 min to obtain a cured film. The cured film was then placed in a tubular resistance furnace and, under nitrogen protection, the temperature was increased to 800°C at a heating rate of 1°C / min and kept constant at this temperature for 90 min to obtain a composite membrane electrode.
[0075] Comparative Example 1
[0076] Delete step 2) in Example 1, and the rest is the same as Example 1.
[0077] The composite membrane electrodes of Example 2-23 and Comparative Example 2-3 are the same as Example 1 except for different experimental parameters (see Table 1).
[0078] Preparation of the battery:
[0079] Taking the composite membrane electrode obtained in Example 1 as an example,
[0080] A lithium-ion battery was assembled using a composite membrane electrode as the negative electrode, a lithium sheet as the positive electrode, a commercial lithium hexafluorophosphate electrolyte as the electrolyte, and a PP-PE-PP three-layer separator as the battery separator.
[0081] The experimental parameters of Examples 1-23 of the present application and Comparative Examples 2-3 are shown in Table 1.
[0082] Table 1
[0083]
[0084]
[0085] “ / ” means none.
[0086] Testing and analysis
[0087] Under the same conditions, the capacity of the composite membrane electrodes prepared in the above Examples 1-23 and Comparative Examples 1-3 was tested. The specific test method is as follows:
[0088] Flexibility test: The composite membrane electrode is bent. The composite membrane electrode with a bending angle greater than 90° is a qualified electrode, and the composite membrane electrode with a bending angle less than 90° is an unqualified electrode.
[0089] Capacity test: Let the packaged battery stand for 12 hours, then -1 Charge and discharge at a constant current for 5 times at a low current, and take the average discharge capacity of 3-5 cycles as the battery capacity.
[0090] The test results are shown in Table 2.
[0091] Table 2
[0092] Flexibility test results Capacity test results Example 1 180° <![CDATA[762mAh g -1 ]]> Example 2 175° <![CDATA[741mAh g -1 ]]> Example 3 178° <![CDATA[612mAh g -1 ]]> Example 4 116° <![CDATA[408mAh g -1 ]]> Example 5 158° <![CDATA[548mAh g -1 ]]> Example 6 164° <![CDATA[691mAh g -1 ]]> Example 7 147° <![CDATA[714mAh g -1 ]]> Example 8 151° <![CDATA[668mAh g -1 ]]> Example 9 136° <![CDATA[598mAh g -1 ]]> Example 10 174° <![CDATA[654mAh g -1 ]]> Embodiment 11 158° <![CDATA[574mAh g -1 ]]> Example 12 166° <![CDATA[518mAh g -1 ]]> Embodiment 13 148° <![CDATA[601mAh g -1 ]]> Embodiment 14 132° <![CDATA[722mAh g -1 ]]> Embodiment 15 154° <![CDATA[742mAh g -1 ]]> Example 16 130° <![CDATA[551mAh g -1 ]]> Embodiment 17 125° <![CDATA[692mAh g -1 ]]> Embodiment 18 134° <![CDATA[444mAh g -1 ]]> Embodiment 19 169° <![CDATA[547mAh g -1 ]]> Embodiment 20 180° <![CDATA[648mAh g -1 ]]> Embodiment 21 180° <![CDATA[702mAh g -1 ]]> Embodiment 22 175° <![CDATA[688mAh g -1 ]]> Embodiment 23 171° <![CDATA[695mAh g -1 ]]> Embodiment 24 168° <![CDATA[702mAh g -1 ]]> Comparative Example 1 / <![CDATA[458mAh g -1 ]]> Comparative Example 2 91° /
[0093] Results and Discussion
[0094] It can be seen from Table 1-2 that the flexibility of the composite membrane electrode of Example 1-24 is significantly better than that of the composite membrane electrode of Comparative Example 1-2, and the battery prepared by using the composite membrane electrode of Example 1-24 has a higher capacity, which is significantly better than the battery of Comparative Example 1-2. This is because during the preparation process of the composite membrane electrode of Example 1-24, after preparing the casting liquid, the solution in the casting liquid is removed, which promotes the phase separation of the casting film dissolution to form a wet membrane with a network structure that penetrates each other, which not only provides a good electrolyte transmission channel, but also relieves the deformation stress of the composite membrane electrode, thereby ensuring the composite membrane The flexibility of the electrode, and in the subsequent curing and carbonization process, the organic matter in the wet film (organic carbon source, thickener, etc.) will undergo pyrolysis reaction to release small molecular compounds (such as H2O, NH3, etc.), which can form a rich pore structure, provide a large specific surface area, and enhance the capacity of active substances, thereby increasing the effective utilization of active substances and further improving the capacity of the electrode. In addition, in the process of carbonization, carbon atoms will rearrange to form a carbon skeleton structure, which can be used for the load of active substances, reduce the risk of volume expansion of active substances and contact with electrolytes, and enhance the safety performance of the battery.
[0095] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0096] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a composite membrane electrode, characterized in that: include: The conductive agent, the active material, the organic carbon source, the thickener and the solvent are mixed to obtain a casting solution; removing the solvent in the casting solution to obtain a wet film; The wet film is solidified and carbonized to obtain a composite membrane electrode.
2. The method according to claim 1, characterized in that The mass ratio of the organic carbon source, the viscosity enhancer, the conductive agent and the active material is (10-18):(5.26-17.65):(0.1-1):(0.1-1).
3. The method according to claim 1 or 2, characterized in that: Based on the total mass of the casting solution, the mass proportion of the organic carbon source is 5%-25%; and / or, The residual carbon rate of the organic carbon source is 35%-55%; and / or, The organic carbon source includes polyacrylonitrile.
4. The method according to claim 1 or 2, characterized in that: The degree of polymerization of the tackifier is 13-96; and / or, The viscosity increasing agent comprises polyvinyl pyrrolidone; and / or, The conductive agent includes at least one of graphene, carbon nanotubes and carbon black; and / or, The active material comprises at least one of silicon dioxide, tin dioxide, ferric chloride, tin chloride and silicon; and / or, The solvent includes N,N-dimethylformamide.
5. The method according to claim 1 or 2, characterized in that: The step of removing the solvent in the casting solution to obtain a wet film comprises: After the casting liquid is scraped, it is placed in an aqueous slow-release agent, so that the solvent in the casting liquid enters the aqueous slow-release agent to obtain a wet film.
6. The method according to claim 5, characterized in that The thickness of the scraping film is 50 μm-300 μm; and / or, The aqueous sustained-release agent comprises water and a sustained-release agent, and based on the total mass of the aqueous sustained-release agent, the mass proportion of the sustained-release agent is 40%-80%; and / or, The sustained-release agent includes at least one of ethanol, ethylene glycol and N,N-dimethylformamide.
7. The method according to claim 1 or 2, characterized in that: The curing temperature is 180°C-280°C; and / or, The curing temperature rise rate is 1°C / min-3°C / min; and / or, The curing time is 1.5h-2.5h; and / or, The carbonization temperature is 900°C-1200°C; and / or The carbonization heating rate is 3°C / min-4°C / min; and / or, The carbonization time is 50 min-80 min.
8. A composite membrane electrode, characterized in that: The composite membrane electrode is prepared by the method according to any one of claims 1 to 7.
9. The composite membrane electrode according to claim 8, characterized in that: The thickness of the composite membrane electrode is 10 μm-50 μm.
10. A battery, characterized in that: The battery comprises a composite membrane electrode prepared by the method of any one of claims 1 to 7 or a composite membrane electrode as described in claims 8 to 9.